Khảo sát hiện tượng bong bóng trên thị trường vàng thế giới trong giai đoạn trước và sau đại dịch COVID-19: Tiếp cận bằng các kiểm định nghiệm đơn vị phía phải - Trần Thị Tuấn, Anh; Nguyễn Thành, Cả (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This article employs future gold prices in the global gold market from January 2017 to December 2023 to examine the existence of bubbles in the gold market. The statistical method used is the GSADF test by Phillips et al. (2015). The overall testing results across the entire dataset indicate no bubbles in the gold market prior to the global outbreak of COVID-19, but there is evidence of a bubble phenomenon during the onset of the COVID-19 pandemic. By using rolling window frames of the GSADF test, three periods are identified where bubble occurrences in the gold market are evident. Firstly, the period from May 2019 to September 2019 coincides with the U.S. – China trade war. Secondly, the period in July and August 2020, during the peak of the COVID-19 pandemic's rapid global spread, along with the announcement of the U.S. and UK governments banning oil imports from Russia. Thirdly, bubbles were found in March 2022, corresponding to the conflict between Russia and Ukraine. These are all significant political events impacting the entire global financial market, particularly the gold market.
Keywords: Market bubbles; COVID-19 pandemic; Right-tailed unit root test; Global gold market